PENGGUNAAN MEDIA FILM ANIMASI JAMAL LAELI UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA ANAK KELOMPOK A DI TK NEGERI 2 POTO TANO - Alti Krismayani; Fahruddin; Abdul Kadir Jaelani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to improve the speaking skills of group A children in Kindergarten Negeri 2 Poto Tano through the use of Jamal Laeli's animated film media. The type of research used is classroom action research (PTK). The data collection method is observation and documentation with qualitative descriptive data analysis by looking at the learning process and learning outcomes of children's speaking skills. The subjects in this study are group A children at Kindergarten Negeri 2 Poto Tano which totals 16 children. The results of the research on the use of animation film media "Jamal Laeli" in the first cycle were carried out well with a percentage of 62.49% and the results of the use of animation film media "Jamal Laeli" in the second cycle increased to 92% were carried out very well. Then speaking skills in cycle I, the percentage value obtained in the first meeting was 58,9% and in the second meeting was 64.6% with an average percentage value of 61.7%. In the first cycle, there were 11 children in the category of developing according to expectations (BSH) with a percentage value of 69% and 5 children in the category of starting to develop (MB) with a final percentage of 31%. Meanwhile, in the second cycle, the percentage value obtained at the first meeting was 79% which then increased at the second meeting by 93.7% with an average percentage value of 86.3%. And in the second cycle, all students were categorized as very well developed (BSB) with a percentage value of 100%. Thus, it can be concluded that the use of the animation film media "Jamal Laeli" can improve the speaking skills of group A children at Kindergarten Negeri 2 Poto Tano.